Intensitas Inovasi Bisnis dalam Bisnis Jasa Kreatif di Indonesia - Mien Mien; Chrisanty Victoria Layman (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2021)
In Indonesia’s New Normal era, creativity is an important aspect for businesses. Previous research suggests the relationship between team support, individual perceptions, the intensity of team and company innovation on students who have entered the world of work. This study explores the effect of individual perceptions, perceptions of team support on the intensity of service business innovation which is mediated by the intensity of team innovation. Data collection was carried out by distributing online questionnaires to 204 employees who work in creative industry service businesses in Indonesia. The study found that perception of individual creativity skills had a positive effect on perceptions of team support for innovation, and perceptions of team support for innovation had a positive effect on the intensity of company innovation. Furthermore, the relationship between perceptions of team support for innovation and entrepreneurial firm innovation intensity is partially mediated by team innovation intensity.